Strategi Pemasaran STP (Segmenting, Targeting, and Positioning) Sepeda Motor Yamaha NMAX di Indonesia - Jamira, Anaseputri; Iskandar, Fadil (Universitas Batanghari Jambi, 2025)
This study aims to analyze the Segmenting, Targeting, and Positioning (STP) Marketing Strategy of the Nmax Automatic Motorcycle produced by Yamaha. To study the Segmenting, Targeting, and Positioning of the Yamaha Nmax Automatic Motorcycle, a descriptive approach is used that describes the implementation of the STP. The types of data used include primary and secondary data. The data that has been collected is then analyzed using a qualitative approach, which involves comparison with relevant theories. The results of the study obtained show that the Yamaha Nmax Automatic Motorcycle divides the market based on demographic and psychographic variables; uses a